تطبيقات النقل الحضري المستدام في مدينة كيوريتيبا البرازيلية والدروس المستفادة من أجل المدن السورية - ميّا رولا; سلوم إيفونا (Latakia University Journal -Engineering Sciences Series, 2019)
إنَّ النمو السكاني والتوسُّع العمراني الذي شهدته معظم المدن على مدى العقود القليلة الماضية، يجعل من توفير نظام لنقل حضري مستدام التحدِّي الهدف الرئيس الذي يواجهه القائمون على قطاع النقل، لما له من دور في حلّ القضايا المحورية المتعلِّقة بالنمو الحضري واستخدامات الأراضي واستهلاك الطاقة وتغيّر المناخ. يدرس هذا البحث تجربة مدينة كيوريتيبا البرازيلية كنموذج لحلّ المشاكل المتعلقة بالنقل الحضري في المدن النامية، ويمكن أن تعتبر بمنزلة حالة مرجعية في تخطيط سياسة النقل المتكامل وتحقيق نظام النقل العمليّ، الكفوء، والفعّال من حيث التكلفة، والذي استند بشكل أساسي على تكامل استعمالات الأراضي مع نظام النقل العام وشبكة الطرق وتعزيز العلاقة مع الإدارة ومشاركة القطاع الخاص. وبناءً على ما تقدَّم، تناول البحث بالترتيب أهم القضايا التي تعالج موضوع النقل الحضري المستدام وفقاً لما يلي: التنمية المستدامة للنقل ومفهوم النقل الحضري المستدام. تحليل تجربة مدينة كيوريتيبا البرازيلية في تحقيق نظام النقل المتكامل. تقييم الآثار البيئية، الاجتماعية والاقتصادية لنظام النقل في كيوريتيبا على المدينة والسكان. الدروس المستفادة من التجربة وإمكانية التطبيق. الاستنتاجات والتوصيات. The population growth and urban sprawl in most cities throughout the last few decades makes from providing sustainable urban transport system, the main challenge the administrators of transport sector confront with, because of its role in solving axial issues of urban growth, land use, energy consumption and climatic change. This research studies the practice of Curitiba city in Brazil as a sample to solve problems related to urban transport in developing cities, and it may be considered as a reference case of integrated transport policy planning and implementing practical, efficient and cost-effective transport system, which depended essentially on the land use integration with public transport system and road network, as well as promoting the relationship with the management and the involvement of private sector. Based on the foregoing, this research contains most important issues that handle the topic of sustainable urban transport, as following: § Sustainable transport development and sustainable urban transport concept. § Analyzing the Curitiba practice in implementing integrated transport system. § Evaluation of environmental, social and economic impacts of transport system in Curitiba on the city and the residents. § Learnt lessons from the practice and potential for implementing. § Conclusions and recommendations.